Marine chemical ecology in benthic environments. Issue 3 (28th September 2018) - Puglisi, Melany P.; Sneed, Jennifer M.; Ritson-Williams, Raphael; Young, Ryan
Abstract : This review highlights the 2013–2015 marine chemical ecology literature for benthic bacteria and cyanobacteria, macroalgae, sponges, cnidarians, molluscs, other benthic invertebrates, and fish. Abstract : Covering: Most of 2013 up to the end of 2015 This review highlights the 2013–2015 marine chemical ecology literature for benthic bacteria and cyanobacteria, macroalgae, sponges, cnidarians, molluscs, other benthic invertebrates, and fish.